Towards developing an integrity framework in Performance Appraisal System (PAS) in the Malaysian public sector: a preliminary analysis from justice and ethical perspectives - Jamaiudin, Norhaslinda; Mohd Adnan, Normala; Aminudin, Rabi'ah; Quddus, S. M. Abdul (Sciedu Press, 2018)
The implementation of Performance Appraisal System (PAS) is seen as a strategic move to foster performance-based work culture in the Malaysia’s public sector. Embedded in pay-for performance system, the new appraisal system which was first introduced in 1992 establishes linkage between pay system, performance and competencies development. However, the chain tying pay to performance appears to be weak. Massive disappointment signals poor implementation as the appraisal system was overshadowed by inappropriate instrument design, rater error, inaccurate rating, bias assessment, etc. These major setbacks have evoked concern over ethical and fairness in the practices of PAS. Occurrence of problems in the implementation of PAS signified erosion of justice and ethics in the practices of PAS, thus lead to growing demand for integrity-based performance assessment system. This preliminary analysis therefore seeks to examine the relationship between ethic, justice and the practices of PAS in the Malaysia’s public sector. Correlation coefficient results disclosed positive association between variables as the instrument used, process employed are moderately associated with ethics and justice dimensions. The appraisal system is likely perceived to be good if fair assessment and ethical supervision were present and vice versa. This study deliberately discusses the aforementioned issues through integrated framework based on organizational justice and work character ethics theories and proposed framework for integrity enhancement in the implementation of PAS. Significantly, this article makes a theoretical contribution towards developing higher integrity capacity which often requires in HRM practice.